Phenolic profiles and antioxidant activity in different organs of Sinopodophyllum hexandrum - Liu, Wei; Zhang, Zheng; Zhang, Tong; Qiao, Qi; Hou, Xiaogai (Frontiers in Plant Science, 2022)
Sinopodophyllum hexandrum is a perennial anti-cancer medicinal plant as unique phytochemical composition podophyllotoxin, which could treat the pneumonic, cervical and testicular cancers. Besides the podophyllotoxin, phenolic substances play a key role in the clinical practice. However, few reports were available in terms of the phenolic compositions and antioxidant activity. In this work, main phenolic compounds were quantified by RP-HPLC in seven organs of S. hexandrum. Simultaneously, total flavonoids and total phenols contents were determined by the sodium borohydride/chloranil-based (SBC) method and the Folin-Ciocalteau colorimetric method, respectively. The three assay methods (DPPH method, ABTS method and FRAP method) were further employed for antioxidant activity evaluation of different organs. Phenolic compositions/total flavonoids contents/total phenols contents/antioxidant activity was observed to have significant differences among different organs (P<0.05), but have a consistent changing rule viz. rhizome>root>fruit>flower>leaf>stem>petiole. Furthermore, a correlation analysis was employed and indicated that a positive correlation existed between phenolic compositions contents and antioxidant activity. Obviously, rhizome had high phenolic compositions contents and strong antioxidant activity with the low DPPHIC50 value of 23.52 μg/mL, high ABTS value of 1137.82 μmol equiv. Trolox/g and high FRAP value of 685.76 μmol equiv. Trolox/g. Therefore, rhizome is recommended as a preponderant medicinal organ, and root is proposed as a substitute raw material resource for natural antioxidant agents in functional food, medicine and chemicals. This study provided a new insight into the utilization extension of S. hexandrum resources.